EFFEK PENAMBAHAN ADRENALIN 1:80.000 DALAM LIDOKAIN 2% TERHADAP TEKANAN DARAH PADA ANESTESI BLOK N ALVEOLARIS INFERIOR - Abdul Rochim (Fakultas Kedokteran Gigi Universitas Jember, 2010)
Vasoconstrictive agents are added to local anesthesitics, used in orofacial surgery and dentistry for elimination of negative effect of local anesthetics on local sirculation in the place of anesthesiaadministration. Adrenalin is one of vasoconstrictive agens usually used to make greater effect of local anaesthetics. This study was undertaken to know about the effect of adrenalin addition 1:80,000 in Lidocain 2% on blood pressure in dental clinical use. Material and Methods: A total of 222 healthy volunteers were included in this randomized double blind clinical trial. They were locally injected as block anaesthesia of the lower jaw. Blood pressure (diastole and systole) is measuremed pre and 5minutes post injected. Result: Mean of blood pressure pre injected 110.14/74.77 mmHg, and blood pressure 5 minutes post injected 111.14/74.35 mmHg. There was statistical and clinical not significantly difference on diastole (p>0.05). There was statistical significantly difference on systole (p<0.05) but noton clinical only 1 mmHg difference